The Federal Home Loan Bank System and U.S. housing finance - W. Scott Frame (Federal Reserve Bank of Atlanta, 2016)
This paper examines the role of the Federal Home Loan Bank (FHLB) System in the U.S. housing finance system. This cooperatively owned government-sponsored enterprise has changed markedly over the past 25 years as a result of membership liberalization and the demise of thrift institutions. Today, despite its name, size, and principal activities, the FHLB System actually provides little targeted support to the housing sector. Instead, recent research highlights the role of the FHLB System as a provider of subsidized general liquidity to its members, including the very largest commercial banking organizations. This role was especially pronounced during the onset of the recent financial crisis and gave rise to the perception of the FHLB System as having become the "lender of next-to-last-resort."
Keywords: G21; G28; 330; residential mortgages; government-sponsored enterprises; liquidity